Andreia : studies in manliness and courage in classical antiquity - Rosen, Ralph Mark.; Sluiter, I. (Mnemosyne, Supplements, 2003)
This volume examines the use of a central concept in the self-definition of any Greek speaking male: Andreia , the notion of courage and manliness. The nature and use of value terms quickly leads the researcher to core issues of cultural identity: through a combination of lexical or semantic and conceptual studies the discourse of manliness and its role in the construction of social order is studied, in a variety of authors, genres, and communicative situations. This book is of interest to students of the classical world, the history of values, gender studies, and cultural historians.